A New Approach to Evaluate Reproductive Traits in Batch-Spawning Fishes of Indeterminate Fecundity and Asynchronous Oocyte Maturation. Issue 4 (2nd October 2021) - Hôrková-Žitňanová, Kristína; Švolíková, Kristína; Haruštiaková, Danka; Kováč, Vladimír
Abstract: Fishes are characterized by a great diversity of reproductive strategies that often make fecundity evaluation difficult. Unlike marine fishes, a single consensual concept of terminology and definitions is lacking for freshwater fish fecundity. Several approaches are known from scientific literature for evaluating fecundity in batch spawning fishes of indeterminate fecundity and asynchronous oocyte maturation. These methodological differences impose a bias on the outputs of comparative studies of fecundity. For both theoretical and practical reasons, accurate fecundity data are required to inform the decision-making process in terms of environmental policy and the related applications for the control of non-native species and the conservation management of native species and ecosystems. The main aim of the present study was to review briefly the existing fecundity-evaluation methods, to test among-method compatibility, and to develop a new approach that aims to make fecundity evaluation more systematic and transparent. A simulated 'test' dataset demonstrated considerable variability in the results obtained from the various existing approaches. The literature review and our analyses revealed a need for standardization. Thus, a new approach is proposed here that is based on multiple sampling throughout the reproductive cycle; provides greater overall detail of the species' reproductive traits and permits inter-population comparisons.